The Impact of Financial Management Behavior, Locus of Control, and Religiosity Toward Investment Decisions During Covid-19 Pandemic: A Study of Genta Muallaf Community in Bali - Rahma Yudi Astuti; Suyanto Suyanto; Diajeng Nurul Falah; Ani Nurul Imtihanah (Al Tijarah, 2022)
The Covid-19 pandemic has affected many economic sectors to decline; one of them is investment. However, this sector is still becoming the center of attention especially for investors. Several factors role and influence the emotional attitudes in investment decision-making such as financial management behavior, locus of control, and religiosity. This study aims to determine the impact of financial management behavior, locus of control, and religiosity in investment decision-making during the Covid-19 pandemic. This was quantitative research that included Genta Muallaf community as the subject. The data were collected by distributing questionnaires, then were analyzed using the IBM SPSS 20 test tool. The results showed that financial management behavior did not fully affect the investment decision-making, while locus of control partially influenced the investment decision-making since both internal and external control factors greatly influenced the human situation itself, and religiosity also did not fully affect the investment decision-making during the Covid-19 pandemic since religious aspects have not been fully implemented in this community. Therefore, it is necessary to further make the financial management behavior as a proposed medium for it can influence more in investment decision-making such as: age, education, and culture aspects. Especially, Genta Muallaf community is expected to be able to foster the society through holding on Islamic law, to manage its financial based on needs instead of desires, and most importantly to always remember God in every decision-making.